Factors Determining the Perceived Security Dimensions in B2C Electronic Commerce Website Usage: An Indonesian Study - Santos Marianus; Syaiful Ali (Universitas Muhammadiyah Yogyakarta, Indonesia, 2021)
Research aims: This study aims to analyze the perceived security dimensions and build a research model using perceived ease of use and perceived usefulness as variables mediating the link between perceived security and the intention to use Indonesia's B2C e-commerce websites. Design/Methodology/Approach: Using a purposive sampling approach, this study conducted an online survey of respondents who had done online transactions, such as business-to-customer (B2C) transactions. Research Findings: The study's results showed that perceived security significantly correlated with buyers' intention to use B2C websites. Theoretical contribution/Originality: This study contributes to developing and validating key dimensions of perceived security and their constructs. Mediation effect test results from TAM, which were perceived ease and perceived use, indicated that only the perceived usefulness variable significantly mediated the relationship between perceived security and intention to use B2C e-commerce websites. Perceived use's mediation was not supported. Practitioner/Policy implication: This research empirically supports the perceived security construct as a second-order construct involving confidentiality, availability, non-repudiation, and privacy. Research limitation/Implication: This study used data from Indonesian individuals, which may differ from other countries' characteristics. It may limit the research' finding generalization. Research aims: This study aims to analyze the perceived security dimensions and build a research model using perceived ease of use and perceived usefulness as variables mediating the link between perceived security and the intention to use Indonesia's B2C e-commerce websites.Design/Methodology/Approach: Using a purposive sampling approach, this study conducted an online survey of respondents who had done online transactions, such as business-to-customer (B2C) transactions.Research Findings: The study's results showed that perceived security significantly correlated with buyers' intention to use B2C websites.Theoretical contribution/Originality: This study contributes to developing and validating key dimensions of perceived security and their constructs. Mediation effect test results from TAM, which were perceived ease and perceived use, indicated that only the perceived usefulness variable significantly mediated the relationship between perceived security and intention to use B2C e-commerce websites. Perceived use's mediation was not supported.Practitioner/Policy implication: This research empirically supports the perceived security construct as a second-order construct involving confidentiality, availability, non-repudiation, and privacy.Research limitation/Implication: This study used data from Indonesian individuals, which may differ from other countries' characteristics. It may limit the research' finding generalization.